Development of Differentiated Teaching Modules Based on Learning Styles in Project IPAS to Improve Students’ Collaboration Skills - Paramitha Yemima Boroallo; I Komang Werdhiana; Lilies N. Tangge; Sitti Aminah; Ratman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a differentiated teaching module based on students' learning styles in the Project-Based Learning of Natural and Social Sciences (IPAS) to improve collaboration skills. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes five phases: analysis, design, development, implementation, and evaluation. The subjects of the study were Grade X students at SMK Negeri 1 Parigi, with 19 students from the Akuntansi dan Keuangan Lembaga (AKL) program as the experimental class and 19 students from the Desain Pemodelan dan Informasi Bangunan (DPIB) program as the control class. Research instruments included expert validation sheets, practicality questionnaires, cognitive assessment tests (pretest and posttest), and observation sheets for collaboration skills. Validation results showed that the module achieved a validity level of 83%, categorized as valid. The module’s practicality was rated at 92% by teachers and 95% by students, both classified as highly practical. Regarding effectiveness, a comparison of posttest scores between the experimental and control groups yielded a Cohen’s d of 0.93, indicating a large effect on students’ cognitive outcomes. Additionally, within the experimental group, a comparison of pretest and posttest collaboration scores resulted in a Cohen’s d of 0.89, also classified as a large effect. These findings demonstrate that the differentiated teaching module effectively enhances students’ 21st-century skills, particularly collaboration.